The Dynamics of Blame Attribution toward China and Planned Behaviour in Australian COVID-19 Compliance - Shim, KyuJin; Zhang, Dashi (New Ideas Concerning Arts and Social Studies Vol. 3, 2025)
In times of crisis and uncertainty, individuals often attribute blame to certain entities or people. The process of blame attribution plays a significant role in shaping public perception and behaviour during a crisis. During COVID-19, public perceptions of government effectiveness and transparency have influenced blame attribution. This study examines the relationship between blame attribution and the Theory of Planned Behaviour (TPB) elements in influencing compliance with COVID-19 public health measures in Australia. It reveals that blaming individuals, rather than governments, surprisingly increases support for governmental regulations, highlighting the complex interplay between blame attribution and public adherence to health policies. The study underscores the importance of subjective norms and behavioural control in shaping public responses. Key findings indicate that while blame attribution towards different entities affects compliance behaviours, subjective norms and behavioural control significantly influence both self-protection intentions and support for government regulations. These results suggest that understanding the dynamics of blame attribution and TPB elements is crucial for developing effective health communication strategies and public policy design, ultimately enhancing societal adherence to essential regulations during health crises.